PENGARUH LINGKUNGAN KERJA FISIK DAN NON FISIK TERHADAP STRES KERJA KARYAWAN PT CITRA ABADI SEJATI - Ani Maryani; Rochmad Fadjar Darmanto; Anik Ariyanti; Sunarso Sunarso (Sekolah Tinggi Manajemen IMMI Jakarta, 2022)
This study aims to determine the influence of the physical work environment and nonphysical work environment on employee work stress at PT Citra Abadi Sejati. This research was conducted at PT Citra Abadi Sejati in a population of 550 employees. A sample of 85 people was taken from stratified sampling techniques. The data collection method uses observation and dissemination of questionnaires. Data analysis method with validity test, reliability test, model test, and classical assumption test. The results showed that the physical work environment has a positive and significant influence on employee work stress. Likewise, the nonphysical work environment has a positive and significant influence on the work stress of PT Citra Abadi Sejati employees.